The saint, the storm, and the ship: diving into the Corsican maritime ex voto - Botcazou, Hélène (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
This article presents a survey carried out in 2018 within the research framework of the author’s defended PhD Dissertation, on the sailing trade coasters of the Corsican shores between the 16th and the 20th c. Few treaties and albums from the 18th and the 19th c. represent Corsican ships. A review of Corsican ex voto representations allows a look on the day-to-day coastal trade from the south of France or the northern part of Italy. The goal was to search for corresponding pictures from Corsica in the maritime ex voto curated in the churches and chapels of the island. This research led to the identification of a two-masted gondola ship that seems associated to the island.